Perlindungan Hukum Terhadap Anak Korban Terlantar Ditinjau Dari Undang-Undang Nomor 35 Tahun 2014 Tentang Perlindungan Anak (Studi Kasus Dinas Pemberdayaan Perempuan Dan Perlindungan Anak Provinsi Sumatera Utara) - Cibro, Hamdani (Universitas Islam Sumatera Utara, 2022)
Children are an inseparable part of human survival and the sustainability of a nation and state. In the Indonesian constitution, children have a strategic role which is explicitly stated that the state guarantees the rights of every child to survival, growth, and development as well as protection from violence and discrimination. A child needs complete affection, guidance, protection from his parents, this is in accordance with the provisions of Human Rights (HAM). One of the universal rights of children is the right to obtain protection due to physical, mental violence, neglect or mistreatment (exploitation) and sexual abuse as well as the right to obtain protection from discrimination and punishment. The formulation of the problem in this study are: 1). How is the legal protection for neglected child victims in terms of Law Number 35 of 2014 concerning Child Protection, 2). How is the implementation of legal protection for neglected child victims in North Sumatra, 3). How barriers to women's empowerment and child protection services in North Sumatra province in protecting neglected children and how to overcome them. The results of the study can be stated that children get legal protection in the women's empowerment and child protection services by assisting in solving cases of children who have been abandoned by their mothers until they are finished. Keywords :Legal Protection, Victims, Abandoned Children